2020
DOI: 10.36348/sjef.2020.v04i09.004
|View full text |Cite
|
Sign up to set email alerts
|

Community Empowerment Strategy in Handling Efforts of Stunting in Malutu Village, Hulu Sungai Selatan

Abstract: This study aims to determine how the role of human development cadres (KPM) in handling stunting and community empowerment strategies in handling stunting in Malutu Village. The method used in this research is a combination research that combines quantitative methods and qualitative methods to be used together in a research activity, so that more comprehensive, valid, reliable and objective data are obtained. Data were collected by interview, area mapping and documentation. Interviews were conducted with key f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…The lack of public awareness about the dangers of stunting also became a challenge for posyandu cadres in dealing with stunting cases in the area. 17 During the COVID-19 pandemic, cadres did not use the proper tools to measure toddler body height, which may affect the measurement results. 18 Body length and height should be measured using an infantometer and a stature meter, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of public awareness about the dangers of stunting also became a challenge for posyandu cadres in dealing with stunting cases in the area. 17 During the COVID-19 pandemic, cadres did not use the proper tools to measure toddler body height, which may affect the measurement results. 18 Body length and height should be measured using an infantometer and a stature meter, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…8 Hamdie, N.A. et al 15 • Pemberdayaan masyarakat yang dilakukan dengan penyerapan anggaran • Peningkatan kapasitas sumber daya manusia melalui dukungan dari pemerintah kabupaten hulu sungai Selatan • Menjalin komunikasi antar pihak terkait • Membuat rencana kerjasama dalam penanganan stunting. 9 Januarti, L.F., Alvin., A.…”
Section: Nounclassified
“…Faktor eksternal meliputi faktor lingkungan fisik, sosial budaya, ekonomi, politik, kekerabatan, pendidikan, nilai, budaya dan teknologi. Penelitian yang dilakukan oleh Hamdie 15 menghasilkan konsep bahwa strategi pemberdayaan masyarakat di Desa Malutu dilakukan dengan analisis SWOT yang dengan meningkatan kapasitas sumber daya manusia melalui dukungan dari pemerintah kabupaten hulu sungai selatan dan menjalin komunikasi antar pihak terkait serta membuat rencana kerjasama dalam penanganan.…”
Section: Pembahasanunclassified
“…Community mobilization through cadres is the right strategy that can be used to reduce stunting. This strategy was obtained after a SWOT analysis was carried out which showed that posyandu cadres are the closest part of the community who have good communication skills even though in implementation they experience various obstacles both from internal cadres and external cadres 9 .…”
Section: Exploration Of the Role Of Posyandu Cadres In The Achievemen...mentioning
confidence: 99%